Studying properties of Lagrangian bounds for many-to-many assignment problems - Litvinchev, I. [UNESP]; Rangel, S. [UNESP]; Mata, M. [UNESP]; Saucedo, J. [UNESP] (Maik Nauka/interperiodica/springer, 2009)
Classical and modified Lagrangian bounds for the optimal value of optimization problems with a double decomposable structure are studied. For the class of many-to-many assignment problems, this property of constraints is used to design a subgradient algorithm for solving the modified dual problem. Numerical results are presented to compare the quality of classical and modified bounds, as well as the properties of the corresponding Lagrangian solutions.